2002
DOI: 10.1063/1.1508438
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of boron reactivation in doped silicon from Hall effect and spreading resistance techniques

Abstract: In this work, a series of 13 boron implants were performed into Czochralski silicon substrates with doses of 2ϫ10 14-1.6ϫ10 15 cm Ϫ2 at energies of 10-80 keV. The boron was deliberately clustered with a 750°C anneal of 10 or 30 min and the electrical activation of the boron implants was determined following a second anneal at 750 or 850°C with a Hall effect system with certain samples also being analyzed with a spreading resistance technique. Analysis of the reactivation rates allows for the determination of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Actually, the electrical measurements for quantifying the BIC dissolution can be affected by scattering effects by B clusters on the mobility of charge carriers, which alters the determination of the active B amount. 6,[93][94][95][96] To properly measure the BIC dissolution energetics, we used the diffusion criterion together with a proper rate equation model able to fit the chemical profiles, to simulate the B diffusion and to extract the clustered B amount produced by a controlled I supersaturation into MBE grown Si samples containing various B doped regions. 97 It was clearly shown that B clusters dissolve following two distinct paths with different energy barriers (3.6 or 4.8 eV) and rates, the slowest one (with the 4.8 eV barrier) being present only for B concentration above the solid solubility.…”
Section: B-i Clusters Formation and Dissolutionmentioning
confidence: 99%
“…Actually, the electrical measurements for quantifying the BIC dissolution can be affected by scattering effects by B clusters on the mobility of charge carriers, which alters the determination of the active B amount. 6,[93][94][95][96] To properly measure the BIC dissolution energetics, we used the diffusion criterion together with a proper rate equation model able to fit the chemical profiles, to simulate the B diffusion and to extract the clustered B amount produced by a controlled I supersaturation into MBE grown Si samples containing various B doped regions. 97 It was clearly shown that B clusters dissolve following two distinct paths with different energy barriers (3.6 or 4.8 eV) and rates, the slowest one (with the 4.8 eV barrier) being present only for B concentration above the solid solubility.…”
Section: B-i Clusters Formation and Dissolutionmentioning
confidence: 99%
“…The formation of B clusters in highly B-doped Si is a well-known phenomenon. [24][25][26] The characteristics of the B clusters formed by B implantation are as follows. It is known from resistivity and SIMS measurements that B clusters are formed in the case of a doping level of approximately 10 19 cm −3 or more.…”
Section: A Origin Of B-h Complexesmentioning
confidence: 99%
“…It is important to notice that for these experiments the concentration of boron in the as-implanted sample is notably higher than the boron solubility limit in monocrystalline Si (~ 4 × 10 17 cm -3 at 600 °C [12]). Thus the fact that a part of the B atoms did not diffuse can be explained considering that during the annealing the immobile atoms formed boron-interstitial-clusters (BICs), whose properties have been the object of theoretical [13][14][15] and experimental [16][17][18][19][20] studies. Fig.…”
Section: E+21 1e+20 1e+19mentioning
confidence: 99%